Goldie - Miles, Ellen (Miles, Ellen. Puppy place, 2005)
Charles and Lizzie Peterson love puppies. They want a puppy of their own more than just about anything. They know dogs are a lot of work. But their Mom still doesn't think their family is ready for a puppy. Then, Goldie arrives. She is a sweet golden retriever who needs a home. Goldie is very young. She doesn't know how to be a good puppy yet. Will Charles and Lizzie be able to help her?